Observation on the therapeutic effect of decompression surgery with proximal nail plate trephination in 61 cases of subungual hematoma - WANG Huafeng; HE Xin; REN Tiansheng; LIU Yihua; MA Zhansheng; DUAN Feng (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To explore the clinical effect and prognosis of decompression surgery with proximal nail plate trephination for the treatment of subungual hematoma. [Methods] A total of 61 patients with subungual hematoma treated at the Dermatology Clinic of Henan Provincial Armed Police Corps Hospital between March 1, 2016, and April 20, 2024, were enrolled. According to the proportion of the area of the nail hematoma to the nail area, and the severity of the fluctuation sensation and swelling pain of the hematoma, decompression surgery with proximal nail plate trephination was performed to drain the blood under digital nerve anesthesia. Postoperative routine dressing changes were performed, and therapeutic outcomes were observed. [Results] Seven days after the surgery, the effective rate was 100%, with complete recovery in 56 cases (91.80%) and marked improvement in 5 cases (8.20%). Follow-up through in-person consultations or WeChat at 1-3 month post-surgery revealed no significant nail plate defects or cosmetic deformities. [Conclusion] Decompression with proximal nail plate trephination is effective for subungual hematoma, with a favorable prognosis.